The Adoption of AI Technology in Police Station Services: A Case Study of Nongchok Metropolitan Police Station - โพธิ์เกษม ภนิดา; นุชอุดม เฉลิมพล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The study of police station services to keep up with AI to be consistent and keep up with the era of artificial intelligence (AI), Nong Chok Metropolitan Police Station is a medium-sized police station located in the suburban area of Bangkok. It serves a community that has diverse cultures and experiences as well as an increasing workload of reports and providing services to the public continuously. This situation necessitates the adaptation of the agency in managing public services. The study of The Adoption of AI Technology in Police Station Services in order to align with and advance alongside the era of Artificial Intelligence (AI), a case study of Nongchok Metropolitan Police Station, aims to study and analyze the current public services at the police station using a mixed research methodology, descriptive analysis by using qualitative research and quantitative research methods. The researchers planned mixed research by using interviews and using questionnaires as research tools. The sample group is 127 people who reported the incident at Nongchok Metropolitan Police Station, members of the general public, and police officers. It was found that the police organized to serve the public systematically and used the AI (Artificial Intelligence) system. There was also development on application that allows the public to contact and use services at the police station conveniently, quickly, and easily. They can express their opinions on the services at the police station to keep up with AI using the case study of Nongchok Metropolitan Police Station. Overall, the mean was 4.27 with a standard deviation of 0.73, which is at the highest level. When considering each aspect, the highest was police behavior, followed by police personality and caring, service mind, police station service system, and the use of technology.